Meningkatkan Hasil Belajar Pendidikan Agama Katolik Siswa Kelas VII-A SMP Swasta Anugerah Kasih Lewoleba Melalui Metode Tanya Jawab - Nuli, Theresia; Henga, Dorothea (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
The purpose of this study was to determine the improvement in learning outcomes of class VII-A students at Anugerah Kasih Lewoleba Private Middle School in the subject of Catholic Religious Education through the Question and Answer method. This study uses a type of classroom action research. This classroom action research was conducted at Anugerah Kasih Lewoleba Private Middle School class VII-A through two cycles, namely cycle I was implemented on September 10, 2024 and cycle II on September 17, 2024. The subjects of the study were 13 class VII-A students. The techniques used in this study were observation and testing. The action plan for each cycle was carried out through four stages, namely the planning, implementation or action, observation and reflection stages. The results of this study indicate that there was an increase in learning outcomes obtained, starting from the pre-cycle, cycle I and cycle II. With the average value of the pre-cycle class reaching 72.5%, cycle I 74.6%, and cycle II reaching 100%. Thus, the application of the question and answer method can improve the learning outcomes of class VII-A students at Anugerah Kasih Lewoleba Private Middle School.